The Role of Attraction Factors in Recreational Shopping Gratification: Case of Colombo, Sri Lanka - Veneka Logenthiran; Susantha Amarawickrama (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
This paper sets out to question: What attraction factors influence recreational shopping gratification. An online questionnaire survey was administered to 220 young adult consumers from two shopping malls in the city of Colombo. A narrative inquiry was employed by conducting 30 interviews from the same sample to light up the research question as to the second step. Exploratory Factor Analysis followed by correlation and regression analysis and content analysis were used as methods of analysis. The result of the research highlighted the importance of socialization, ambience and safety and security towards increasing recreational shopping gratification, while socialization plays the most important role in gratification. Meanwhile, as revealed from content analysis, fun and entertainment is an attractive factor in the Sri Lankan context. The outcomes of the study, using a mixed-methods approach, would enrich both the theory and practice of developing a consumer-friendly environment to increase gratification in recreational shopping.